17.4k views
3 votes
Which first step for solving the given system using substitution results in an equation without fractions?

[3x+y=9

15x-3y = 1

Solve for x in the first equation.

Solve for y in the first equation.

Solve for x in the second equation.

Solve for y in the second equation.

User Warlax
by
5.2k points

2 Answers

1 vote

Answer:

It's B (the one above is right)

Explanation:

User Bumhan Yu
by
5.7k points
3 votes

Answer:

Solve for y in the first equation.

Explanation:

Given

3x+y=9

15x-3y = 1

Required

Determine the first step to avoid fractions

From the list of given options, the option that best answered the question is to Solve for y in the first equation.

Solving for y will let you substitute the expression for y in the second equation

Going by that:- Solve for y in the first equation.


3x + y = 9

Subtract 3x from both sides


3x - 3x + y = 9 - 3x


y = 9 - 3x

Substitute 9 - 3x for y in the second equation


15x - 3y = 1 becomes


15x - 3(9 - 3x) = 1


15x - 27 + 9x = 1

Collect like terms


15x + 9x = 1 + 27


24x = 28

Divide both sides by 24


(24x)/(24) = (28)/(24)


x = (28)/(24)

Divide numerator and denominator by 4


x = (7)/(6)

Substitute 7/6 for x in the
y = 9 - 3x


y = 9 - 3 * (7)/(6)


y = 9 - (7)/(2)

Solve fraction


y = (18-7)/(2)


y = (11)/(2)

User Miqdad
by
5.7k points